PERAN PERSEPSI PEMAKAI BAHASA TERHADAP PEMBINAAN BAHASA INDONESIA - ., Ngatmini; ., Suyitno (SASINDO, 2013)
Indonesian either as national language, as well as instruction language expected to be an efective tools of cummunication for every user or citizen. Every language user has a multiple knowledge, comprehension, acceptance, toward the language. There are a positive user toward language that communicationg by do their best in using the Indonesian language, pay attention to the applicable rules of the language. However, there are user that regard the language as simple thing so they underestimate the rules. So that they lack of attention to the rules of the language to cummunicate. Language attitude can be changed by some ways through principle together between goverment and developer team and Indonesian language bilder. This attitude will be base of someone perception. The positive user perception toward language will contribute Indonesian coaching, on the other way the negative user perception will effecte some disfluencies or impede on the couching languege process. Keywords: role, language user, language bilder